(untitled) (Bangladesh Journal of Botany, 2024)
Many rivers throughout Bangladesh are now under threat due to both human-made and natural causes. In this context, we describe the Buriganga river system, its uses of the river, its level of pollution, and its sources of pollution. The present condition of the Buriganga water and its surrounding areas soils and plants might not be suitable for fisheries and irrigation; it has been observed that sampling points of 9,10,11 were highly polluted, with sampling point 7 with the highest water pH value (7.19), in sampling point 11 EC value was found (799 μS/cm) with other physicochemical parameters and Fe, Cd, Cr and Zn content in plant and soil samples were comparatively high at sampling point 9 and 11. In the studied area, the correlation coefficient of heavy metal content among soil and water, the Cr concentration (0.0289mg/l), was highly significant; it has been indicated that heavy metals were uptake by soil. Bangladesh J. Bot. 53(3): 589-596, 2024 (September)